Suppressed OsPsbS1 expression triggers rice leaf senescence mediated by reactive oxygen species - Wang, Quanxiu (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.